2012
DOI: 10.2215/cjn.02650312
|View full text |Cite
|
Sign up to set email alerts
|

Association of Depression and Antidepressant Use with Mortality in a Large Cohort of Patients with Nondialysis-Dependent CKD

Abstract: SummaryBackground and objectives Depression is common and is associated with higher mortality in patients with ESRD or CKD (stage 5). Less information is available on earlier stages of CKD. This study aimed to determine the prevalence of depression and any association with all-cause mortality in patients with varying severity of nondialysis-dependent CKD.Design, setting, participants, & measurements This is a retrospective study of a national cohort of 598,153 US veterans with nondialysis-dependent CKD stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 36 publications
4
39
3
Order By: Relevance
“…material B3) [7,57,78,85,86,87]. This reduced our number of summary measures from 55 to 16, and only 3 of the measures involved cardiovascular samples.…”
Section: Resultsmentioning
confidence: 99%
“…material B3) [7,57,78,85,86,87]. This reduced our number of summary measures from 55 to 16, and only 3 of the measures involved cardiovascular samples.…”
Section: Resultsmentioning
confidence: 99%
“…[41][42][43][44][45] Our results indicated a high burden of sleep disturbances in kidney patients. In addition, female gender and having low MCS scores may influence sleep quality.…”
Section: Discussionmentioning
confidence: 98%
“…[52][53][54] Briefly, study subjects were identified by using measurements of serum creatinine in the Veterans Affairs (VA) Decision Support System National Data Extracts Laboratory Results file 55 56 Patients with eGFR,60 ml/min per 1.73 m 2 on at least two occasions no less than 3 months apart and available BMI measurements within this period were included in the study. Cohort entry was defined as the date of the first baseline eGFR used to define CKD status.…”
Section: Study Populationmentioning
confidence: 99%